Peningkatan Motivasi dan Hasil Belajar Kognitif Biologi dengan Menggunakan Model Pembelajaran Kooperatif Tipe The Learning Cell - Nurcholifatun, Nurcholifatun (Biocaster : Jurnal Kajian Biologi, 2024)
The lack of student participation in learning is caused by teachers not paying attention to students' psychological conditions, so that students experience difficulties in learning which has an impact on low motivation and student learning outcomes. The effectiveness of learning, learning motivation and learning outcomes need to be improved through a learning process using a cooperative model of The Learning Cell type, namely a concept that places more emphasis on raising questions which is the key to learning. The purpose of this research is to determine the increase in motivation and cognitive learning outcomes of students using the cooperative learning model type The Learning Cell. The type of research used is classroom action research which consists of two cycles, each cycle consisting of two meetings. This research measures the results of observations of the implementation of teacher and student activities, motivation and cognitive learning outcomes of students using observation sheets on the implementation of teacher and student activities, as well as questionnaires and evaluation tests. The results of the research show that the percentage of implementation of the results of observing teacher activities in cycle I was 82.57% which was included in the good category and cycle II increased with a percentage of 89.28% in the very good category, while the results of observing the implementation of student activities in cycle I was with a percentage of 60. % in the quite active category and increased in cycle II with a percentage of 85% in the very active category. Student motivation was obtained from the distribution of questionnaires in the first cycle which was in the good category at 80.60% and in the second cycle it increased to 82.56%, still in the good category. Student cognitive learning outcomes are obtained from evaluation tests that have been prepared and distributed to students at the end of each cycle, in cycle I it was 65%, so students were not yet said to be classically complete and continued in cycle II which experienced an increase of 87%, so student learning outcomes on the subject of interdependence in ecosystems, it is stated to be classically complete. Based on these results, it can be concluded that by implementing the cooperative learning model of The Learning Cell type, it can increase the motivation and cognitive learning outcomes of Biology students at SMP Negeri 2 Kayangan.